Identifikasi Disfungsi Foot Step dan Comb pada Eskalator Shelter Skytrain di Stasiun Kereta Bandar Udara Internasional Soekarno-Hatta, Cengkareng - Kurniawati, Zulina; Astuti, Annisa Puji; Septiawan, Dwi Cahya; Yosafat, Yosafat; Clarissa, Gita; Bakhtiar, Ramadhani indika (Jurnal Teknik Mekanikal Bandar Udara, 2023)
An escalator is one of the upward and downward lifting devices consisting of separate steps that can run a long path like a rail or chain driven by a machine. The benefits of escalators are considerable, for example, it can move a lot of people and do not hold a time span, especially during congested hours. Therefore,damage to the escalator is quite disruptive to the comfort of passengers. One important part of the escalator that is quite vulnerable to damage is the footstep. Footstep that serves as a place for passengers to stand and step on. When the author made direct observations, several problems were found in the Soekarno-Hatta International Airport Train Station escalator unit. The problem is that the step runs unbalanced, the comb is broken and there is a sound of collision between steps. Based on research to determine the cause of damage to the escalator step and comb unit, it was concluded that there was a collision between the step and the comb on the escalator at the Soekarno-Hatta International Airport Train Station, which reduced the performance of the escalator because there were indications in the form of broken roller chain, broken rail/track where the roller chain runs, not straight roller connecting plate on the roller chain, then there are different settings between the left and right roller chains, finally the lack of the connecting chain between the gearbox and the drive wheel.